Animasi Interaktif Pembelajaran Sel pada Hewan dan Tumbuhan - Rasyid, Yuli Lestari; Sugiarso, Brave A.; Rumagit, Arthur (Universitas Sam Ratulangi, 2021)
Abstract — The field of education is one of the users of technology that is growing, the use of information technology in the field of education is one of the learning media through the multimedia field. The linkage of technology and education has begun to be applied in subjects at school, but for example, biology subjects still use book learning media. This causes students to sometimes carry quite heavy books. Therefore, learning media is needed that can be taken anywhere and done anytime. The purpose of this research is to create an interactive learning animation application through an Android mobile application. This research uses the MDLC (Multimedia Development Life Cycle) software development method. The application has been successfully created and contains interactive animations of cell learning in animals and plants. In this application there are 2D images and explanations, the application is made using the Unity application, the application can only be accessed on android mobile smartphones. Keywords — Interactive Animation; Multimedia Development Life Cycle; Animal Cells; Plant Cells. Abstrak — Bidang pendidikan merupakan salah satu pengguna teknologi yang semakin berkembang, pemanfaatan teknologi informasi dalam bidang pendidikan salah satunya media pembelajaran melalui bidang multimedia. Keterkaitan teknologi dan bidang pendidikan mulai diterapkan dalam mata pelajaran yang ada di sekolah, namun contohnya mata pelajaran biologi masih menggunakan media pembelajaran buku. Hal ini menyebabkan siswa terkadang membawa buku cukup berat. Oleh sebab itu diperlukan media pembelajaran yang bisa dibawa kemana saja dan dikerjakan kapan saja. Tujuan penelitian ini untuk membuat aplikasi animasi interaktif pembelajaran melalui aplikasi mobile Android. Penelitian ini menggunkan metode pengembangan software MDLC (Multimedia Development Life Cycle). Aplikasi telah berhasil dibuat dan berisi Animasi interaktif pembelajaran sel pada hewan dan tumbuhan. Dalam aplikasi ini terdapat gambar 2D dan penjelasannya, pembuatan aplikasi dibuat menggunakan aplikasi Unity, aplikasi hanya dapat diakses pada smartphone mobile android. Kata kunci — Animasi Interaktif; Multimedia Development Life Cycle; Sel Hewan; Sel Tumbuhan